Cannabinoid Receptor 2 as Antiobesity Target: Inflammation, Fat Storage, and Browning Modulation - Rossi, Francesca; Bellini, Giulia; Luongo, Livio; Manzo, Iolanda; Tolone, Salvatore; Tortora, Chiara; Bernardo, Maria Ester; Grandone, Anna; Conforti, Antonella; Docimo, Ludovico; Nobili, Bruno; Perrone, Laura; et al. (The journal of clinical endocrinology and metabolism, 2016)
Context:Obesity is associated with a low-grade inflammatory state and adipocyte (ADP) hyperplasia/hypertrophy. Obesity inhibits the “browning” of white adipose tissue. Cannabinoid receptor 2 (CB2) agonists reduce food intake and induce antiobesity effect in mice. A common missense CB2 variant, Q63R, causes CB2-reduced function.Objective:To evaluate the influence of CB2 receptor on the modulation of childhood obesity and of ADP activity and morphology.Design:CB2-Q63R variant was analyzed in obese Italian children. The effects of an inflammatory stimulus and those of drugs selectively acting on CB2 were investigated on in vitro ADPs obtained from mesenchymal stem cells of adult healthy donors or from sc adipose biopsies of adult nonobese and obese subjects.Setting:Department of Women, Child and General and Specialist Surgery of the Second University of Naples.Patients or Other Participants:A total of 501 obese Italian children (age 11 ± 2.75). Twelve healthy bone marrow donors (age 36.5 ± 15); and 17 subjects, 7 lean (age 42 ± 10) and 10 obese (age 37.8 ± 12) underwent sc adipose tissue biopsies.Main Outcome Measures:Effects of CB2 stimulation on adipokine, perilipin, and uncoupling protein-1 expression.Results:The less-functional CB2-R63 variant was significantly associated with a high z-score body mass index. CB2 blockade with AM630 reverse agonist increased inflammatory adipokine release and fat storage and reduced browning. CB2 stimulation with JWH-133 agonist reversed all of the obesity-related effects.Conclusion:CB2 receptor is a novel pharmacological target that should be considered for obesity.AbstractAdipocyte cultures obtained from adipose biopsies of non-obese and obese subjects and treated with drugs acting on CB2 receptor revealed that CB2 stimulation inhibits inflammation and fat storage and induces browning.